2015
DOI: 10.4238/2015.december.8.16
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted selection of Fusarium wilt-resistant and gynoecious melon (Cucumis melo L.)

Abstract: ABSTRACT. In this study, molecular markers were designed based on the sex determination genes ACS7 (A) and WIP1 (G) and the domain in the Fusarium oxysporum-resistant gene Fom-2 (F) in order to achieve selection of F. oxysporum-resistant gynoecious melon plants. Markers of A and F are cleaved amplified polymorphic sequences that distinguish alleles according to restriction analysis. Twenty F 1 and 1863 F 2 plants derived from the crosses between the gynoecious line WI998 and the Fusarium wilt-resistant line MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The cut roots were then soaked in a buffer containing Fusarium spore suspension (2.5 × 10 6 spores/mL) for 30 min before being replanted in pots with clean soil mixture (peat: vermiculite = 3:1) for cultivation. Symptom evaluation was conducted 7, 14, and 21 days after inoculation, and disease severity was classified on a scale from 0 to 5 [ 57 ] (where level 0 indicates no symptom, level 1 represents yellowing or wilting of cotyledons; level 2 indicates yellowing or wilting of the first true leaf; level 3 indicates the yellowing or wilting of two true leaves; level 4 indicates yellowing or wilting of at least half of plant leaf; and level 5 indicates plant death). After recording disease severity at 21 days post- inoculation, the resistance status of each individual was determined based on their disease rank: individuals with ranks ranging from 0 to 1 were classified as resistant, while those with ranks exceeding 2 were classified as susceptible.…”
Section: Methodsmentioning
confidence: 99%
“…The cut roots were then soaked in a buffer containing Fusarium spore suspension (2.5 × 10 6 spores/mL) for 30 min before being replanted in pots with clean soil mixture (peat: vermiculite = 3:1) for cultivation. Symptom evaluation was conducted 7, 14, and 21 days after inoculation, and disease severity was classified on a scale from 0 to 5 [ 57 ] (where level 0 indicates no symptom, level 1 represents yellowing or wilting of cotyledons; level 2 indicates yellowing or wilting of the first true leaf; level 3 indicates the yellowing or wilting of two true leaves; level 4 indicates yellowing or wilting of at least half of plant leaf; and level 5 indicates plant death). After recording disease severity at 21 days post- inoculation, the resistance status of each individual was determined based on their disease rank: individuals with ranks ranging from 0 to 1 were classified as resistant, while those with ranks exceeding 2 were classified as susceptible.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf damage was used as a main index to evaluate resistant/susceptible phenotypic traits. The standard reported by Gao et al (2015) and Xu et al (2016) was further improved and implemented with a few modifications. We classified the phenotypes of plants according to a 0-4 scale as follows: level 0, no disease symptoms, i.e., immune (I); level 1, slight disease symptoms, featured by less than 25% of leaves with disease symptoms, with normal plant growth, i.e., highly resistant (HR); level 2, slight wilt symptoms, featured by 25-50% of leaves with disease symptoms, i.e., resistant (R); level 3, moderate wilt symptoms, featured by 50-90% of leaves with disease symptoms, i.e., susceptible (S); and level 4, completely wilted or dead plants, i.e., highly susceptible (HS; Supplementary Figure 2).…”
Section: Disease Assessment and Statistical Analysismentioning
confidence: 99%
“…The ANOVA results showed that the broad-sense heritability (h 2 ) was 87.19% across the 2 years (Table 1), suggesting that the genetic effect played a predominant role in the phenotypic variation of FW resistance in bottle gourd. We divided the DI into five levels (Supplementary Figure 2): immune (level 0), highly resistant (level 1), resistant (level 2), susceptible (level 3), and highly susceptible (level 4), according to relevant previous studies (Gao et al, 2015;Xu et al, 2016). Only a tiny percentage of accessions had DI values less than 15% (8 in 2019 and 1 in 2020), whereas the majority of the accessions were within the range of 15.01-45% (35 in 2019 and 28 in 2020) and 45.01-75% (37 in 2019 and 42 in 2020).…”
Section: Phenotypic Analysis Of Fw Resistance In the Natural Populationmentioning
confidence: 99%
“…In addition, two male-sterile watermelon lines were developed via backcrossing using both the 'ms' male sterility and 'dg' delayed-green seedling markers (Zhang et al, 1996). Similarly, a melon breeding line with both F. oxysporum-resistance genes and gynoecious traits was successfully selected using molecular markers associated with the sex determination genes ACS7 and WIP1 and the F. oxysporum-resistance gene Fom-2 (Gao et al, 2015 Table 5. Molecular markers associated with disease resistance and other traits used for marker-assisted selection in melon, watermelon, and cucumber lines with multiple lateral branching traits were selected from a backcrossing population of cucumber using five associated markers (Fazio et al, 2003;Robbins et al, 2008).…”
Section: Marker-assisted Selection (Mas)mentioning
confidence: 99%